MOTHER STATUS, NUTRITIONAL STATUS, AND PSYCHOSOCIAL STIMULATION AS DETERMINANT FACTORS OF COGNITIVE DEVELOPMENT AMONG UNDER FIVE YEARS OLD CHILDREN - Purwanti, Rachma; Margawati, Ani; Widjanarko, Bagoes (Jurnal Psikologi, 2020)
Early childhood development (ECD) has long-life effects on an individual, that were essential for human capital accumulation and contribute to economic growth. This study aimed to analyzed factor that contributed to cognitive development. This study used cross sectional design by purposive sampling technique. Sample study were 61 early childhood 4-5 years old. Data collected by conducting interviews, observation, and anthropometric measurements. Nutritional status data were collected by using anthropometry, psychosocial stimulation was collected by using EC-HOME inventory instrument, and cognitive development was measured using instrument developed by the Department of National Education of Indonesia. Data analysis includes descriptive test, correlation, and regression. There were 23% of children with underweight, 78.7% children get high risk of psychosocial stimulation, and 57.6% have a good cognitive development. The correlation test showed that there were significant association between the psychosocial stimulation and nutritional status to the cognitive development. Regression model also showed that cognitive development was predicted by maternal status (working mothers/housewife), nutritional status, and psychosocial stimulation.